2013
DOI: 10.1002/jbm.b.33038
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of antibacterial Ag nanostructures on TiO2 nanotube layers by magnetron sputtering

Abstract: To reduce the incidence of postsurgical bacterial infection that may cause implantation failure at the implant-bone interface, surface treatment of titanium implants with antibiotic materials such as silver (Ag) has been proposed. The purpose of this work was to create TiO2 nanotubes using plasma electrolytic oxidation (PEO), followed by formation of an antibacterial Ag nanostructure coating on the TiO2 nanotube layer using a magnetron sputtering system. PEO was performed on commercially pure Ti sheets. The Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 94 publications
0
34
0
1
Order By: Relevance
“…Hence, the results of reduced cell attachment for untreated TiO 2 nanotube surfaces in our study may have been affected by EO gas sterilization. However, our previous studies with same method of sterilization, EO gas [24], [25], showed that there was no indication of compromised cellular attachment on the sterilized samples. Therefore, the effects seen here likely are not due solely to the method of sterilization used.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Hence, the results of reduced cell attachment for untreated TiO 2 nanotube surfaces in our study may have been affected by EO gas sterilization. However, our previous studies with same method of sterilization, EO gas [24], [25], showed that there was no indication of compromised cellular attachment on the sterilized samples. Therefore, the effects seen here likely are not due solely to the method of sterilization used.…”
Section: Discussionmentioning
confidence: 78%
“…All the specimens were sterilized using ethylene oxide (EO) gas at a temperature of 55°C for 1 h before each experiment. EO gas sterilization was chosen for sterilization of TiO 2 nanotubes in the cell experiments because previous experiments we have verified that it has no effect on cell health [24], [25].…”
Section: Methodsmentioning
confidence: 99%
“…This can be done by tailoring topography on the nanoscale [12,35,36], by incorporating varied amounts of Ag in similar structures [13,16,37,38], or by pursuing alternative strategies for antibacterial surfaces, thoroughly surveyed in recent reviews [10,[14][15][16]22]. Although history has proven that with persistence and some chance, great discoveries can be made, the possibility of this occurring will undoubtedly be greater if more parameters can be screened in a faster and cheaper way [17,18,[39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…TiO 2 nanotube implants for bone interface were surface treated with silver to act as an antibiotic material and prevent any bacterial infection during postsurgical periods [80]. Synthetic polymers such as polyacrylates, polyglycolides and polycaprolactone copolymers dominate over natural polymers like collagen and gelatin; based on their capability to attain a sustained release of therapeutic agents.…”
Section: Nanoparticles In Bone Tissue Engineeringmentioning
confidence: 99%